Some Inequalities on ‘Useful’ Mean g-deviation with Applications in Information Theory - Pankaj Prasad Dwivedi, Dilip Kumar Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The objective of this correspondence is to offer an elaboration of some latest inequalities' findings, in which we have given a new improvement of ‘useful’ Jensen's inequality, as well as utilization in the theory of information. In linear spaces, for convex functions constructed on a convex subset, an improvement inequality of Jensen's is provided. For ‘useful mean deviation and ‘useful’ divergences, we provide robust lower bounds as well as the ‘useful’ mean h-absolute deviation, and lastly, we have given applications of divergence measure. Uniqueness for the ‘useful’ KL-Divergence and ‘useful’ Jeffreys divergence is obtained.